1996
DOI: 10.1046/j.1365-2362.1996.2420580.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a soluble form of neutral endopeptidase‐24.11 (EC 3.4.24.11) in human serum: enhancement of its activity in serum of underground miners exposed to coal dust particles

Abstract: A previous epidemiological study has reported the elevation of a serum metalloendopeptidase activity for underground coalminers exposed to chronic inhalation of coal mine dust particles. In this work, we have unambiguously characterized this activity as neutral endopeptidase (EC 3.4.24.11) using five different criteria. The apparent molecular weight of 100,000 g mol-1 calculated for the serum peptidase using Western blots or direct binding of the neutral endopeptidase 24.11 inhibitor [125I]-RB104 to the enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
1
10
1
Order By: Relevance
“…This speculation is supported by several previous studies that increased NEP activities in serum were observed from underground miners exposed to coal dust particles (Soleilhac et al, 1996) or patients with pulmonary inflammatory diseases, such as sarcoidosis and adult respiratory distress syndrome (Johnson et al, 1985; Almenoff et al,1986). Increased NEP activities in serum may reflect local tissue damage with subsequent shedding of membrane-bound enzymes and an abnormal release from the airways in response to lung injury (Soleilhac et al, 1996). In this study, significant increases of soluble NEP activity following exposures suggest that membrane-bound NEP in airways was modified or impaired structurally and functionally.…”
Section: Discussionsupporting
confidence: 64%
“…This speculation is supported by several previous studies that increased NEP activities in serum were observed from underground miners exposed to coal dust particles (Soleilhac et al, 1996) or patients with pulmonary inflammatory diseases, such as sarcoidosis and adult respiratory distress syndrome (Johnson et al, 1985; Almenoff et al,1986). Increased NEP activities in serum may reflect local tissue damage with subsequent shedding of membrane-bound enzymes and an abnormal release from the airways in response to lung injury (Soleilhac et al, 1996). In this study, significant increases of soluble NEP activity following exposures suggest that membrane-bound NEP in airways was modified or impaired structurally and functionally.…”
Section: Discussionsupporting
confidence: 64%
“…Infusion of the metalloprotease inhibitor thiorphan into the hippocampus of rats resulted in a significant increase in the amount of A␤ and in the deposition of the longer more amyloidogenic form, A␤42, reportedly through the inhibition of A␤ degradation by NEP. NEP and ACE have been reported to reside predominantly on the cell surface, although a soluble form of NEP is also present in serum and cerebral spinal fluid (43)(44)(45)(46). A recently identified thiorphan-sensitive NEP homo-logue SEP/NL1/NEPII is expressed both as a membrane-bound and secreted protease (47)(48)(49).…”
Section: Resultsmentioning
confidence: 99%
“…23 Possible cellular origin of soluble NEP are neutrophils and alveolar epithelial cells. 31 NEP is known to be an integral membrane protease, and the mechanism for the release of a soluble form is unknown. One possible origin of soluble NEP is by the shedding process, which occurs in many eukaryotic cells with membrane-bound proteins being released with portions of plasma membrane or as proteolipid aggregates.…”
Section: Discussionmentioning
confidence: 99%